Association between interindividual variability in training volume and strength gain - Ema, Ryoichi; Saito, Itaru; Akagi, Ryota (Frontiers in Physiology, 2022)
This study aimed to examine the association between interindividual variability in strength changes and in training volume. A total of 26 untrained men completed 4-weeks of isometric knee extension (KE group, n = 12) and hip flexion (HF group, n = 14) training. Each training session comprised four sets of ten isometric contractions, 3-s contractions every 20 s. Training volume, which was defined as impulse during contractions, and maximal voluntary contraction (MVC) torque during KE and HF were evaluated. Based on the magnitude of MVC torque changes, the participants were divided into the high and low responders (n = 13; KE = 6 and HF = 7 per responders). The MVC torque changes (KE, 20.8%; HF, 22.4%) and total training volume did not significantly differ between the two groups. A higher training volume was demonstrated in the low responders than the high responders. The total training volume was positively associated with the MVC torque changes in low responders (r = 0.869, 95% confidence interval [0.610, 0.960], P < 0.001), but not in high responders (r = 0.229, 95% confidence interval [−0.368, 0.693], P = 0.451), KE or HF group. Results showed that training volume was an important factor in determining the magnitude of strength gains in low responders, and MVC torque could improve by approximately 20% with the use of the study protocol regardless of joint actions involved during training.